Deflagration in empty tank being rinsed with water. Issue 4 (2nd May 2019) - Britton, Laurence G.; McDavid, Benjamin C.
Abstract : A deflagration occurred inside a 200‐gal (0.757 m 3 ) atmospheric mixing vessel during the course of apparently normal operations. The vessel had previously been used to dilute 70% aqueous tert ‐butyl hydroperoxide ( t ‐BHP) with deionized water. Ten minutes earlier the mixed batch had been transferred out and the vessel had been given a brief rinse with deionized water about 4 minutes after the transfer. The deflagration occurred soon after starting the second of two deionized water rinses. Although the hinged vessel lid was forced open and damaged there were no injuries or chemical exposures since no personnel were in the area at the time. The incident was caused by a faulty metering system that overcharged sodium hypochlorite (bleach) solution to the deionized water supply. The roughly 100‐fold overcharge of bleach resulted in a vigorous, gassy reaction with t ‐BHP in the mixing vessel. The reaction generated a gas‐phase mixture comprising mostly acetone plus about 90% oxygen. The ignition energy of a replicated mixture was 0.015 mJ, similar to that of optimum hydrogen‐air, but with poor upward mixing of acetone the ignition energy could have been as small as 2 μJ. The source of ignition could not be identified with certainty; the "least improbable" scenario was considered to be a spark from an electrically charged slug of rinse water falling through an electrically charged mist that had formed during the gassy reaction. © 2019 American Institute of Chemical Engineers Process Saf Prog: e12054 2019